2020
DOI: 10.18203/2349-3933.ijam20204966
|View full text |Cite
|
Sign up to set email alerts
|

A study on clinical profile of acute stroke

Abstract: Background: Stroke or cerebrovascular accident is one of the leading causes of morbidity and mortality in adult life. Ischemic strokes are most common type of strokes and they account for 80-85% of cerebrovascular accidents worldwide. Hypertension, diabetes, dyslipidemia and smoking have been identified as major risk factors. Present study was undertaken to evaluate the clinical and investigation profile of different types of strokes.Methods: A total of 100 patients with brain stroke from November 2015 to Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Hypertension was observed in 77.3% of ICH cases. 29 The second comorbidity seen in present study was T2DM. this study reported 40 cases of T2DM in a cohort of 235 SICH.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Hypertension was observed in 77.3% of ICH cases. 29 The second comorbidity seen in present study was T2DM. this study reported 40 cases of T2DM in a cohort of 235 SICH.…”
Section: Discussionmentioning
confidence: 47%
“…28 found higher rates of hypertension as the most prevalent risk factor (72.5%) followed by DM (54.4%) when compared with this study, Itagietal. 29 reported hypertension in 38% cases followed by hypertension with diabetes mellitus in 23%. The other risk factors in descending order in their study were dyslipidemia, smoking, diabetes and alcohol excess.kay et al Hypertension was documented in 47.2% of the entire cohort of patients in study by Kay et al 31 and was the most common risk factor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation